THE INFLUENCE OF PRICE PERCEPTION AND PRODUCT QUALITY ON PURCHASING DECISIONS AT JAGO COFFEE WITH CONSUMER TRUST AS A MODERATING VARIABLE - Rizatullah Ramdani; La Diadhan Hukama (Universitas Putera Batam, 2025)
The purpose of this study is to analyze the influence of price perception and product quality on purchasing decisions with consumer trust as a moderating variable in YARSI University students as consumers of Jago Coffee and its review from an Islamic perspective. This study involved a sample of 180 respondents with a purposive sampling technique. Data collection was carried out through a survey method with a questionnaire and analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method and processed using SPSS and Warp PLS applications. The results of the model evaluation indicate that price perception, product quality, and consumer trust have a high level of suitability and are relevant in predicting their influence on purchasing decisions. The results of this study reveal that price perception and product quality each have a positive and significant influence on purchasing decisions. Furthermore, consumer trust has not been able to moderate the influence of price perception and product quality on purchasing decisions.